Simplified Transformation of Ostreococcus tauri Using Polyethylene Glycol - Sanchez, Frédéric (Genes (Basel), 2019)
Ostreococcus tauri is an easily cultured representative of unicellular algae (class Mamiellophyceae) that abound in oceans worldwide. Eight complete 13–22 Mb genomes of phylogenetically divergent species within this class are available, and their DNA sequences are nearly always present in metagenomic data produced from marine samples. Here we describe a simplified and robust transformation protocol for the smallest of these algae (O. tauri). Polyethylene glycol (PEG) treatment was much more efficient than the previously described electroporation protocol. Short (2 min or less) incubation times in PEG gave >10(4) transformants per microgram DNA. The time of cell recovery after transformation could be reduced to a few hours, permitting the experiment to be done in a day rather than overnight as used in previous protocols. DNA was randomly inserted in the O. tauri genome. In our hands PEG was 20–40-fold more efficient than electroporation for the transformation of O. tauri, and this improvement will facilitate mutagenesis of all of the dispensable genes present in the tiny O. tauri genome.